1996
DOI: 10.1080/095003496154725
|View full text |Cite
|
Sign up to set email alerts
|

Observation of the geometric amplitude factor in an optical system

Abstract: A bstract.By manipulating the discrete optical levels inside an optical resonator, we obtain a classical realization of a twisted Landau ± Zener model.We experimentally demonstrate the geometric amplitude factor in the transition amplitude that arises for this model. We consider in particular the region of parameter space addressed in the original study of the geometric amplitude factor by M. V. Berry [7].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…It has already been suggested that, for example, the Yb atom could be used in conjunction with frequency modulated light [14,20], and it may also prove possible to manipulate the discrete optical levels in a resonator to show the same phenomena [21]. The transformation…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has already been suggested that, for example, the Yb atom could be used in conjunction with frequency modulated light [14,20], and it may also prove possible to manipulate the discrete optical levels in a resonator to show the same phenomena [21]. The transformation…”
Section: Discussionmentioning
confidence: 99%
“…These results can be derived in a similar manner as Eqs. (20), (21), (26), and (27). Thus, the excited-state populations at the crossings lie on just one sinusoid for cosine modulation and on another sinusoid for sine modulation.…”
Section: Excited-state Population At the Nodesmentioning
confidence: 99%
See 1 more Smart Citation
“…Resembling behavior is known in vibrational mechanical modes [6]. In optics, anticrossings (also referred to as avoided crossings) with a gap in the transmission frequency have been reported in liquid-crystal etalons [7] and used to observe the geometric amplitude factor [8]. Crossing of optical resonances was recently reported [9] in spherical cavities.…”
mentioning
confidence: 99%
“…Alternatively, a geometrical phase can be generated by continuously varying the parameters θ and φ in a cyclic fashion [38,39]. Starting from θ = 0 one can perform a cyclic adiabatic evolution on the (θ, φ) plane along a loop C. As predicted by Equations (19)- (22), the qubit state |11 then acquires the geometrical phase…”
Section: B Stirap-based Geometrical Phase Gatementioning
confidence: 99%